RESEARCH PROGRESS ON CUTTING TECHNOLOGY OF SIC MONO-CRYSTAL WAFER WITH WIRE SAW - LI Lun; LI ShuJuan; TANG AoFei; LI Yan (Jixie qiangdu)
Having a unique physical characteristics and stable semiconductor properties,silicon carbide（ Si C） monocrystal wafer has been widely used in integrated circuits,space optics and other fields.In manufacturing process of Si C monocrystal wafer,cutting is primary key process,which the cutting costs accounts for more than 50% of the whole wafer processing costs.In this paper,the datum and relevant literature of domestic and foreign were reviewed to,the current research status of Si C cutting technology,especially cutting with wire saw,and cutting equipment were studied.Moreover,the existing problems in Si C cut by wire saw and in cutting equipment was analyzed.It is proposed that the future researching direction of Si C wafer cutting technology by wire saw.